A Comparative User Study of Two Virtual Tour Strategies at the Ruins of São Miguel das Missões - Scalco, Leonardo; Sant'Anna, Manoela Lencino; De Almeida, Gustavo Corrêa; Martins Jr., Renato da Veiga; De Souza, Vinícius Costa (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2023)
The São Miguel Arcanjo Archaeological Site, commonly called ruins of São Miguel das Missões, is one of the main vestiges of the period of the Jesuit Missions of the Guarani around the world, located in the small municipality of São Miguel das Missões, in the northwest of Rio Grande do Sul, Brazil. The Ruins of São Miguel das Missões were declared a World Cultural and Natural Heritage Site by Unesco in 1983 and are part of the Iguassu-Missiones international itinerary, being visited by tourists from all over the world, especially from Argentina, Paraguay, Uruguay and European countries. Despite its historical and cultural importance, visiting the site is inaccessible for many people, for different reasons, especially the lack of financial resources. In this context, providing a virtual tour of the site is extremely relevant for the dissemination and access to this important cultural heritage. As so, this work presents a comparative study of two virtual tour strategies: guided and self-guided. A controlled user experiment was carried out with eleven participants and the results showed no difference in engagement and knowledge of the ruins. As for the preference, the participants opted for the self-guided tour.